Decolonizing Diasporas : Radical Mappings of Afro-Atlantic Literature - Figueroa-Vásquez, Yomaira C (Book collections on Project MUSE., 2021)
"Figueroa-Vásquez analyzes Afro-Latinx and Afro-Hispanic artists from Equatorial Guinea, Puerto Rico, the Dominican Republic, and Cuba, revealing the thematic, conceptual, and liberatory tools these artists offer when read in relation to one another"--